Epilepsy in the onchocerciasis endemic area of Deim Zubeir, South Sudan: a household survey - Mamur, Jurel Payii; Van Cutsem, Gilles; Motto, Sekonjo Juliano Hamid; Jada, Stephen Raimon; Gerber, Tatjana; Bol, Yak Yak; Siewe Fodjo, Joseph Nelson; Colebunders, Robert (Frontiers in Tropical Diseases, 2025)
BackgroundHigh epilepsy prevalence and mortality has been reported in onchocerciasis-endemic areas with suboptimal elimination programs in South Sudan. In Deim Zubeir, an onchocerciasis-endemic area in Western Bahr El Ghazal state, demand for antiseizure medication is high, but epilepsy prevalence has never been investigated.MethodsA two-step household survey was conducted in four locations in Deim Zubeir over two weeks in July 2023. Trained local community volunteers screened household members for epilepsy using four screening questions, assessed blindness, and inquired about family members’ deaths in the past three years. Participants with suspected epilepsy were referred to a medical doctor for confirmation of the diagnosis.ResultsA total of 7,807 individuals in 1,803 households participated in the survey; 180 (2.3%) had epilepsy and 146 (1.9%) were blind in at least one eye. The point prevalence of active epilepsy was 23.1 (95% confidence interval [CI] 20.0-26.6) per 1,000 persons. The median age of persons with epilepsy (PWE) was 25 (interquartile range [IQR] 20-31.5) years; median age at onset of seizures was 14 (IQR 9-19) years; 36.4% of PWE had siblings with a history of seizures; 5.3% were blind in at least one eye; 40.7% had burn lesions and 24.7% had skin lesions compatible with onchocerciasis; 55% met the criteria for onchocerciasis-associated epilepsy (OAE). The mortality rate of PWE was 182.4 per 100,000 person-years (95%CI 132.8-232.0) and the epilepsy case fatality rate was 64.1 (95% CI 47.2-80.9) per 1,000 PWE per year. PWE were six times more likely to die within one year than people without epilepsy. Their median age of death was 21.5 (IQR 16-34) years compared to 41 (IQR 7-60) years for people without epilepsy.ConclusionThe prevalence of epilepsy and epilepsy-related mortality in Deim Zubeir is high, likely because of ongoing Onchocerca volvulus transmission. Strengthening the local onchocerciasis elimination program and ensuring consistent access to epilepsy care is urgently needed to prevent OAE and epilepsy-related mortality and morbidity. It is necessary to increase advocacy and funding to ensure early identification of epilepsy and uninterrupted, free access to antiseizure medication for PWE in this remote, impoverished area.